The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1600-0838.2011.01317.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of eccentric training on hand strength in subjects with lateral epicondylalgia: a randomized‐controlled trial

Abstract: The main aim of this study was to evaluate the short-term effects of daily eccentric exercises on functional pain-free hand strength in subjects with long-term lateral epicondylalgia. Forty-two subjects with lateral epicondylalgia were randomly assigned either to a 6-week home exercise regimen receiving eccentric training for their wrist extensors and a forearm band or to a control group receiving a forearm band only. The main outcomes were pain-free hand-grip and wrist-extensor strength at mid- and end-interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 26 publications
1
61
0
10
Order By: Relevance
“…Given the paucity of the available data (one RCT with moderate-quality evidence for pain relief in the intermediate term 112 ), the overall low level of evidence as determined using the GRADE principles (see Table 24) and the subsequent publication of four relevant RCTs, 18,164,166,172 we conclude that there is insufficient evidence at present to demonstrate either benefit or lack of effect of exercises for LET. All of the subsequent RCTs identified are recent publications 18,164,166,172 In addition, seven RCTs were identified that were included in an intermediate-/low-quality systematic review.…”
Section: Exercisesmentioning
confidence: 97%
See 1 more Smart Citation
“…Given the paucity of the available data (one RCT with moderate-quality evidence for pain relief in the intermediate term 112 ), the overall low level of evidence as determined using the GRADE principles (see Table 24) and the subsequent publication of four relevant RCTs, 18,164,166,172 we conclude that there is insufficient evidence at present to demonstrate either benefit or lack of effect of exercises for LET. All of the subsequent RCTs identified are recent publications 18,164,166,172 In addition, seven RCTs were identified that were included in an intermediate-/low-quality systematic review.…”
Section: Exercisesmentioning
confidence: 97%
“…All of the subsequent RCTs identified are recent publications 18,164,166,172 In addition, seven RCTs were identified that were included in an intermediate-/low-quality systematic review. 137,141,149,151,157,162,163 An updated, good-quality systematic review of exercises for LET is needed before stronger recommendations can be made; however, we suggest that some consideration should also be given to conducting large-scale, good-quality RCTs of clearly defined exercise modalities with sufficient follow-up periods (to 1 year).…”
Section: Exercisesmentioning
confidence: 99%
“…Sobre la base de los criterios de selección de nuestra RS, sólo 36 artículos fueron incluidos (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)27,29,31,(33)(34)(37)(38)(39)(40)(43)(44)(45)61,(73)(74)(75)(82)(83)(84). El riesgo de sesgo se evaluará utilizando la herramienta propuesta en el "Cochrane Handbook" para Ensayos Clínicos Aleatorizados (91).…”
Section: Evaluación Del Riesgo De Sesgo De Los Artículos Seleccionadosunclassified
“…En base a los resultados de nuestra búsqueda agrupamos los artículos seleccionados en las siguientes comparaciones: ejercicio terapéu-tico sólo versus otra intervención sola (15,18,33,61), ejercicio terapéutico sólo versus un programa de tratamiento (7,9,12,17,19,20,29,34,37,39,43,45,(73)(74)(75) y programa de tratamiento que incluya ejercicio terapéuti-co versus otro programa de tratamiento (8,11,14,16,(21)(22)(23)25,27,31,38,40,44,(82)(83)(84).…”
Section: Intervenciones Y Comparacionesunclassified
See 1 more Smart Citation